Avaliação econômica do cooperativismo na cadeia produtiva do leite no Vale do São Lourenço (MT) - Jesus, Esdras Warley Nunes de (2016)
The study aimed to carry out an economic evaluation of dairy farming of the Vale São Lourenço-MT through the study of Cooperative COMAJUL with industrial headquarters in Jaciara, MT. Therefore, the quantitative and qualitative information in order to analyze the milk production chain were verified. It was found that the milk production sector (farmers), the milk processing sector (cooperative), the distribution and consumption of processed milk and dairy products. The study presents qualitative analysis to check for points of bottlenecks within this production chain and proposes strategies for improving income and welfare of the region. In addition, it sought to evaluate quantitatively the relationship between supply and prices. In qualitative view, it was observed that during the production of fresh milk in the years 2003-2015, the production chain was in successor threat justified by points arising bottlenecks in rural properties (within the gate) and not in the management model chosen by the cooperative (upstream and downstream). The quantitative data indicated the significance of the production of packaged milk Type C and organization of participation together to production markets, retail and wholesale.